Clinical significance of the series of CYP2C9*non3 variants, an unignorable predictor of warfarin sensitivity in Chinese population - Wang, Dongxu; Wu, Hualan; Dong, Min; Zhang, Qing; Zhao, Anxu; Zhao, Xinlong; Chong, Jia; Du, Minghui; Wang, Yan; Shi, Haifeng; Wang, Shuanghu; Wang, Fang; et al. (Frontiers in Cardiovascular Medicine, 2022)
Gene polymorphisms are critical for variations in warfarin dose. To date, more than 70 CYP2C9 alleles have been identified, . This study was designed to clarify the clinical significance of CYP2C9*non-3 variants to warfarin sensitivity in Chinese Han patients. The entire CYP2C9 gene region was sequenced in 1,993 individuals, and clinical data and VKORC1 genotypes were collected from 986 patients with atrial fibrillation treated with warfarin. The SKAT-O method was used to analyze the effects of CYP2C9*non-3 variants on warfarin sensitivity. A total of 20 CYP2C9 variants were identified, of which four were novel. Carriers with CYP2C9*non-3 variants may have lower warfarin dose requirements, and similar to CYP2C9*3, CYP2C9*non-3 variants are clearly relevant to warfarin-sensitive and highly sensitive responders. Our results showed that, besides CYP2C9*3, the series of CYP2C9*non-3 variants is an unignorable predictor for warfarin sensitivity in Chinese population. From a safety consideration, people carried such variants may need a preferred choice of NOACs when they started anticoagulation therapy.